Correction: Alkoxy radicals generation: facile photocatalytic reduction of N-alkoxyazinium or azolium salts. Issue 24 (7th March 2019) - Capaldo, Luca; Ravelli, Davide
Abstract : Correction for 'Alkoxy radicals generation: facile photocatalytic reduction of N -alkoxyazinium or azolium salts' by Luca Capaldo et al., Chem. Commun., 2019, DOI: ;10.1039/c9cc00035f .